2015
DOI: 10.1007/s11356-015-5953-x
|View full text |Cite
|
Sign up to set email alerts
|

A study on identification of bacteria in environmental samples using single-cell Raman spectroscopy: feasibility and reference libraries

Abstract: We report on our recent efforts towards identifying bacteria in environmental samples by means of Raman spectroscopy. We established a database of Raman spectra from bacteria submitted to various environmental conditions. This dataset was used to verify that Raman typing is possible from measurements performed in non-ideal conditions. Starting from the same dataset, we then varied the phenotype and matrix diversity content included in the reference library used to train the statistical model. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…From 2004, with the advent of confocal microscopy, high-magnification objectives and availability of highly sensitivity detectors, single bacterial identification and imaging through Raman have been explored [28,29]. Studies have reported single bacterial identification for medically and environmentally relevant bacteria like anthrax [30], in urinary tract infection [31], in water pathogens [32,33], in meat-associated pathogens [34], and in many other samples [16,[35][36][37] using multivariate analysis techniques. Raman spectroscopy along with supervised multivariate analysis techniques like support vector machine (SVM) has also been employed to identify TB pathogens, but no studies has reported use of Raman for identification and viability assessment [38].…”
Section: Discussionmentioning
confidence: 99%
“…From 2004, with the advent of confocal microscopy, high-magnification objectives and availability of highly sensitivity detectors, single bacterial identification and imaging through Raman have been explored [28,29]. Studies have reported single bacterial identification for medically and environmentally relevant bacteria like anthrax [30], in urinary tract infection [31], in water pathogens [32,33], in meat-associated pathogens [34], and in many other samples [16,[35][36][37] using multivariate analysis techniques. Raman spectroscopy along with supervised multivariate analysis techniques like support vector machine (SVM) has also been employed to identify TB pathogens, but no studies has reported use of Raman for identification and viability assessment [38].…”
Section: Discussionmentioning
confidence: 99%
“…Raman spectra of a single bacterial cell, also known as single-cell Raman spectrum, represent detailed information of various biomolecules present in the bacterial cells like protein, DNA, carbohydrates, and lipids. Thus, the Raman spectrum of a bacterial cell can be an accurate fingerprint of the bacterial cell type. It offers a significant advantage over existing clinical approaches, especially where the number of bacteria in a biomaterial is limited or very low. This approach can be used directly for samples that are isolated from patients without needing additional cultivation steps, which can affect the result and thus make it less time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Raman microspectroscopy allows exploring intracellular transformations and their features and helps to understand the processes occurring in the cell when studying the properties of the selective interaction of reagents in the cell . Recently, achievements in Raman microspectroscopy have opened up new prospects for the rapid and sensitive detection of bacteria of various types …”
Section: Introductionmentioning
confidence: 99%